2005
DOI: 10.1111/j.1099-1123.2005.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

The Different Types of Assurance Services and Levels of Assurance Provided

Abstract: In 2001 the International Auditing Practices Committee (IAPC, now the International Auditing and Assurance StandardsBoard (IAASB)) commissioned research on the determination and communication of moderate assurance. This research was published in IFAC research monograph No. 1 (2002). Part of this research involved surveying the types of assurance services undertaken by 56 assurance firms from 11 different countries, the levels of assurance at which these assurance services were generally provided, and for those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 22 publications
2
46
1
Order By: Relevance
“…On the other hand, accountants were more likely to indicate the level of assurance and applied a more conservative, cautious, and limited approach to provide low levels, while non-accountants applied a more evaluative approach and provided higher levels. Hasan et al [71] evidenced that many of the accounting firms applied a limited/moderate level of assurance rather than a reasonable/high level. Deegan et al [72,73] found considerable variability in presentation formats and contents across assurance providers; for example, they pointed out that accounting providers were more likely to mention assurance standards.…”
Section: Sustainability Assurancementioning
confidence: 99%
“…On the other hand, accountants were more likely to indicate the level of assurance and applied a more conservative, cautious, and limited approach to provide low levels, while non-accountants applied a more evaluative approach and provided higher levels. Hasan et al [71] evidenced that many of the accounting firms applied a limited/moderate level of assurance rather than a reasonable/high level. Deegan et al [72,73] found considerable variability in presentation formats and contents across assurance providers; for example, they pointed out that accounting providers were more likely to mention assurance standards.…”
Section: Sustainability Assurancementioning
confidence: 99%
“…Here, recent empirical research shows how AAPs tend to indicate a limited level, or a combination of limited and reasonable SR assurance reliability, because they recognize an intrinsic difficulty in the process of SR control. This complexity is due to the mix of qualitative and quantitative information, which can be subjectively interpreted, in the assured documentation (Hasan et al 2005); -the possibility of working with an interdisciplinary team of experts coordinated by the assuror; -type of controls implemented (substantive and control tests, analytical procedures); -the evaluation of audit (residual) risk (possibility of report being materially misstated after the assurance service is completed and an unqualified opinion is issued), as a consequence of its various components (inherent risk, control risk, and detection risk) (Messier et. al.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, the level of assurance declared in the assurance statement is particularly important. Factors determining higher or lower reliability of controls (Hasan et al 2005; International Federation of Accountants (IFAC) 2002) are: -use of selective tests; -limitations of internal control systems; -indicative or conclusive nature of the elements assembled by the assurance provider; -considerable discretion exercised in collecting indicative elements and in drawing conclusions based on verified evidence; -intrinsic nature of the subject matter.…”
Section: Introductionmentioning
confidence: 99%
“…The only certainty is the substantial impossibility of guaranteeing an absolute level of assurance, nor indeed is this foreseen for traditional full audits (Hasan et al, 2005;IFAC, 2002).…”
Section: Introductionmentioning
confidence: 99%